Digital Business Transformation: A Case Study of Singapore - Suhardjo, Suhardjo; Sun, Lee Ho; Pacquiao, Jose Rodrigo (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
In today's digital era, digital business transformation has become a critical factor for the success of companies worldwide. Singapore, as an economic and technological hub in Asia, exemplifies effective implementation of digital transformation in business. This study explores how businesses in Singapore have adopted digital technologies to enhance operational efficiency, expand markets, and provide better services to customers. It focuses on three case studies: Grab, DBS Bank, and Shopee. The research employs a multiple case study approach, leveraging both qualitative and quantitative data from primary and secondary sources, including interviews, surveys, and document analysis. The findings highlight the role of service integration, AI, and data analytics in digital transformation. Grab's evolution into a super app, DBS Bank's digital banking initiatives, and Shopee's mobile-first strategy and live streaming features are examined. The study also addresses challenges such as cybersecurity, data privacy, and the need for a skilled digital workforce. Singapore's strong technological infrastructure, supportive regulations, and dynamic startup ecosystem have enabled businesses to leverage digital technologies effectively. The successful digital transformation of these companies offers valuable insights and can serve as an inspiration for other countries aiming to navigate the digital landscape.